2015
DOI: 10.1097/md.0000000000001722
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Gastric Mucosa in the Distal Part of Esophagus in a Teenager

Abstract: Heterotopic gastric mucosa (HGM) of the esophagus is a congenital anomaly consisting of ectopic gastric mucosa. It may be connected with disorders of the upper gastrointestinal tract, exacerbated by Helicobacter pylori. The diagnosis of HGM is confirmed via endoscopy with biopsy. Histopathology provides the definitive diagnosis by demonstrating gastric mucosa adjacent to normal esophageal mucosa. HGM located in the distal esophagus needs differentiation from Barrett's esophagus. Barrett's esophagus is a well-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Despite this, BPV still fail, especially in a mitral position (30% degeneration at 12-15 years), mainly due to degradation and calcification. Stabilization of tissues by glutaraldehyde promotes cell death, and it has been shown that its activity persists for many months after implantation, slowly releasing active glutaraldehyde monomers that destroy fibrocytes and macrophages that come into contact with the toxic material [10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, BPV still fail, especially in a mitral position (30% degeneration at 12-15 years), mainly due to degradation and calcification. Stabilization of tissues by glutaraldehyde promotes cell death, and it has been shown that its activity persists for many months after implantation, slowly releasing active glutaraldehyde monomers that destroy fibrocytes and macrophages that come into contact with the toxic material [10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…This type of abnormal tissue can be found in many different areas of the gastrointestinal tract including the rectum, gallbladder, cystic duct, and most commonly in the esophagus. If left unchecked, this type of tissue can lead to gastric ulcers due to high amounts of acid secretion as well as fistulous tracts, strictures, and esophageal webs, and rarely can be a precursor to adenocarcinoma [ 10 , 11 , 12 ]. Data in pediatrics about the incidence and prevalence of this finding are rare, but there have been reports of patients as young as 1 year presenting with this type of tissue found at pathology [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, Lupu and colleagues reported the extent of cardiac mucosa and heterotopic gastric mucosa in the distal part of the esophagus in a teenager and pointed out that heterotopic gastric mucosa was mimicking short-segment BE. 31 Considering the congenital component, we reviewed all endoscopic pictures of EGJ in 43 patients aged ≤2 years old. Extent of small tongue-like Z-line without any symptoms of GER was present in a 2-year-old boy (Fig.…”
Section: Is Be a Congenital Or An Acquired Disease?mentioning
confidence: 99%